Use Case Diagram for Enhancing Warehouse Performance at PT. MDA Through the Implementation of 5S, Economic Order Quantity, Safety Stock, and Warehouse Management System - Kurniawan, Michael Radius; Hadiyanto, Hadiyanto; Zulkarnaen, Joe Daniansyah Pahlevi; Harito, Christian (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
An industrial water pump importing company relies on a network of distribution warehouses to efficiently manage the storage and delivery of its products to clients. This paper delves into the operational intricacies of the company, with a primary focus on sustaining a superior level of service to meet customer demands, all while attempting to minimize costs and achieve optimal inventory control. The central aspects explored in this research encompass the meticulous determination of the number of pipes needed and the optimal ordering times. To address this, the Probabilistic Economic Order Quantity (EOQ) method is used and supported by 5S concept, recognized for its ability to provide reasonably accurate estimates crucial for pivotal decision-making in inventory management. The utilization of the Probabilistic EOQ method in this context reflects the company's commitment to adopting sophisticated and proven methodologies to enhance decision-making accuracy and the warehouse area is more suitable by the 5S implementation principles. The research outcomes not only assist in refining the determination of Safety Stock levels but also contribute valuable insights into the precise quantities of goods that should be ordered. With an estimated demand for 196 units of carbon 6" in the following year, a safety stock of 13 units is required, while for carbon 4" with an estimated demand of 119 units, a safety stock of 8 units is required. These upcoming insights could encompass innovative strategies, technological implementations, or advances in supply chain optimization.